2020
DOI: 10.1002/anie.201915281
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial‐DNA‐Targeted IrIII‐Containing Metallohelices with Tunable Photodynamic Therapy Efficacy in Cancer Cells

Abstract: The development of DNA‐targeted photodynamic therapy (PDT) agents for cancer treatment has drawn substantial attention. Herein, the design and synthesis of dinuclear IrIII‐containing luminescent metallohelices with tunable PDT efficacy that target mitochondrial DNA in cancer cells are reported. The metallohelices are fabricated using dynamic imine‐coupling chemistry between aldehyde end‐capped fac‐Ir(ppy)3 handles and linear alkanediamine spacers, followed by reduction of the imine linkages. The length and odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 84 publications
0
33
0
Order By: Relevance
“…[31] As shown in Figure 7, after irradiating the cells pretreated with M5 b for 10 min (white light, 18 Jcm À2 ), strong green fluorescence was observed, suggesting ROSw ere generated efficiently inside of the cells.H owever, negligible fluorescence was detected in the absence of M5 b or light irradiation. Furthermore,s odium azide (NaN 3 ), as pecific 1 O 2 scavenger, [32] decreased the fluorescence intensity significantly,which further confirmed that M5 b generated intracellular 1 O 2 for PDT treatment.…”
Section: Resultsmentioning
confidence: 61%
“…[31] As shown in Figure 7, after irradiating the cells pretreated with M5 b for 10 min (white light, 18 Jcm À2 ), strong green fluorescence was observed, suggesting ROSw ere generated efficiently inside of the cells.H owever, negligible fluorescence was detected in the absence of M5 b or light irradiation. Furthermore,s odium azide (NaN 3 ), as pecific 1 O 2 scavenger, [32] decreased the fluorescence intensity significantly,which further confirmed that M5 b generated intracellular 1 O 2 for PDT treatment.…”
Section: Resultsmentioning
confidence: 61%
“…Li et al . reported the preparation of dinuclear Ir III ‐based triple‐stranded metallohelices targeting mtDNA, showing efficient PDT effect and DNA binding ability [81] . As mentioned earlier, compared with nDNA, mtDNA is more susceptible to oxidative damage, therefore, by directly targeting the mtDNA helix and shortening the distance between cytotoxic substances and mtDNA molecules, the PCT/PDT strategy will show a stronger tumor killing effect.…”
Section: Therapies Of Targeting Mtdnamentioning
confidence: 95%
“…Duan and co‐workers designed linear diamine‐/diimine‐alkyl spacer‐based luminescent helicates/mesocates [ 12 ] with dinuclear Ir(III) centers to target mitochondrial DNA in cancer cells with tunable photodynamic therapy (PDT) efficacy [40] . A family of stable, neutral, green luminescent, saturated triple‐stranded homoleptic helicates and mesocates containing two fac ‐[Ir(ppy) 3 ] cores were prepared by using three terminal aldehyde groups on the fac ‐Ir(ppy) 3 core (L 12 ), and linear diaminealkyl spacer having different chain lengths with the imine‐bond formation.…”
Section: Aliphatic Chain Spacer Based Ligands and Its Sccsmentioning
confidence: 99%